Guía de recursos de arte en Internet - Gallego Lorenzo, Josefa; Morán Suárez, María Antonia (Estudios humanísticos. Geografía, historia y arte, 2001)
The main object of this work is to enrich the understanding of art digital recourses. Proposal of a selection about the current state and developments of specialized intenet-based resources in the art in Spain.